O craque, o sex symbol e o homem de sucesso: a construção da imagem de Neymar no mercado brasileiro de revistas (2010/2011/2012) - Ferraz, Luís Henrique Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aims to cover discursive and imagetic construction of Neymar, footballer that started his career for Santos FC and currently plays for Barcelona FC and the Brazilian National Team. Our goal is to analyze how the Brazilian magazine market has projected the athlete's image on the covers of different publications between 2010/2011/2012. During such period. Neymar was the cover of at least 22 magazines, from distinct themes and journalistic sections as follows: the sports, male, teen female and varieties sections. Therefore, using the methodology framework of the French Discourse Analysis, our main goal it to interpret how each of the selected national magazines has built Neymar's status as a new national celebrity. In short, we seek to scrutinize how the first pages of the Brazilian publications have formed their discourses (verbal and non-verbal), prioriziting a systemic, euphoric and convergent construction for Neymar's celebration as a media personage in Brazil

O presente estudo tem como finalidade abordar a construção discursiva e imagética de Neymar, futebolista que iniciou sua carreira no Santos FC e que atualmente defende o Barcelona FC e a Seleção Brasileira. Nosso objetivo é analisar como o mercado brasileiro de revistas projetou a imagem do atleta em capas de diferentes publicações do país, no triênio 2010/2011/2012. Neste período, Neymar esteve presente em pelo menos 22 capas de revistas, de temáticas e segmentos jornalísticos distintos - a saber: o segmento esportivo, o segmento masculino, o segmento feminino adolescente e o segmento de variedades. Desse modo, utilizando o arcabouço metodológico da Análise do Discurso de linha francesa, nosso foco principal da pesquisa é interpretar como cada revista nacional selecionada construiu o status de Neymar como nova celebridade nacional. Em suma, buscamos esmiuçar como as primeiras páginas das publicações brasileiras formaram seus discursos (verbais e não verbais) priorizando uma construção sistêmica, eufórica e convergente para a celebrização de Neymar como personalidade midiática no Brasil
The football star, the sex symbol, the successful man: the construction of the image of Neymar in Brazilian magazine market (2010/2011/2012)
Keywords: Comunicação; Periódicos; Esportes; Celebridades; Communication